ANALISIS SEMIOTIK DALAM PUISI “AKU INGIN” KARYA SAPARDI DJOKO DAMONO - Reza Muhammad Iqbal; Teti Sobari; Mimin Sahmini (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This Observation function for poetry analysis “Aku Ingin” by Sapardi Djoko Damono with semiotic and description about signified and signifier about that poetry. Poetry is one of the most profound forms of literary work in interpreting all its contents and there are also life values in the process of making it.  The background of the study is based on the author’s interested to analyze Sapardi Djoko Damono's poem “Aku Ingin” as the object to be analyzed, because of the content is a big wishing for became reality but the result is nothing. Basically, interpreting signs or symbols is the basic principle of the semiotic approach. Sensitivity in appreciating a literary work is an understanding of signs, symbols or cues in the poetry itself. In appreciating higher literary works is by doing in-depth studies, namely research.  Analyze the data study: (1) choosing and reading poetry “Aku Ingin” by Sapardi Djoko Damono, (2) analyzing the poem using semiotica approach, (3) describing meaning of that poetry. The results of the poetry analysis include the theme of love and having a sense of love for others with the simplest possible, high level of love is to love the way is it and sometimes a wish is just a vain wish.